On farm Agricultural produce processing: A boon for Indian farming - Mann, Sandeep; Balakrishnan, Renu; Mittal, Sachin; Singh, Rajbir; Chahal, V P (Indian Farming, 2022)
To achieve the goal of “doubling farmers income” there is a need of shifting to entrepreneurship development through primary and secondary processing of agricultural produce at the farm level. These enterprises helps in increasing the income of farmers by20–25%. More number of fellow farmers are required to be linked to one established unit at the community level on profit basis. The major requirements for enhancement in the level of processing are production and availability of good quality raw material, appropriate training on post-harvest technologies, awareness about the benefits of farm level processing, capitalization of the localmarket, and awareness and knowledge of government schemes and subsidies. However, Govt. of India is also promoting these entrepreneurship facilities to budding entrepreneurs through various subsidy schemes such as MUDRA Yojana, PM-FME, PM-KSY etc. ICAR-CIPHET is already contributing and willing to provide hand holding for producers who wish to be the processor.